Exploring the development, evaluation and implementation of complex health interventions to prevent early childhood caries in preschool children: A scoping review protocol. - Peggy C J M van Spreuwel; Milou L C Munk-Overkamp; Linda C Smit; Kirsten A Ziesemer; Cor van Loveren; Geert J M G van der Heijden; Josef J M Bruers; Katarina Jerković-Ćosić (PLoS ONE)
Objective This scoping review aims to identify complex health interventions (CHI's) to prevent early childhood caries (ECC), explore the level of complexity of the identified CHI's, and explore the details of their development, evaluation, and implementation. Introduction Many interventions to prevent ECC have multiple interacting components and can be seen as CHI's. Recent reviews on these interventions have found inconclusive effects, which may be due to differences in the development, evaluation, and implementation of CHI's. Inclusion criteria This scoping review will consider clinical trials reporting CHI's to prevent ECC that starts during pregnancy or in the first year of life. Studies in the English language will be included regardless of the country of origin, sociocultural setting, or context. Methods This review will follow the Joanna Briggs Institute methodology for scoping reviews. An initial search of PubMed identified keywords and Medical Subject Headings terms. A second search of PubMed, Embase, Clarivate Analytics/Web of Science Core Collection, ClinicalTrials.gov, and the Wiley/Cochrane Library will follow. Two independent reviewers will perform title and abstract screening, retrieve and review full-text studies, and extract data. The reference lists of all included sources will be screened for additional CHI's or relevant publications about a specific CHI. Data charting will be utilised based on study characteristics and intervention complexity. A 39-item instrument will be used to explore the details in the description of the CHI's development, evaluation, and implementation. The results will be presented in tables, visual outputs, and a narrative summary in response to the review questions. Discussion The proposed review will generate evidence which may provide a direction for the future design of studies on CHI's to prevent ECC and more complete information for those who want to adopt successful interventions to prevent ECC.